Designing and Implementation Exploration Vehicle Remote Controller Using APRS Protocol - Hongyim, Nimit; Mithata, Somsak (My University, 2018)
The main purposed of this research paper was for implementation of APRS (Automatic Position Report System) Protocol in use with remote controller for controlling Exploration Vehicle where cannot be reached by the conventional wireless network. The research experiment expected result on success communicate between point to point distances over 10Km.
Keywords: APRS; Data Communication; Embedded; GPS